2012
DOI: 10.1007/s12011-012-9396-7
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Arsenic and Its Effects on Fetal Development in the General Population of Dalian

Abstract: To evaluate prenatal exposure to arsenic in the general population and its effects on birth size, we conducted a cross-sectional study in Dalian, China. Arsenic concentration in maternal and cord blood was detected by inductively coupled plasma-mass spectrometry and its effects on birth size were analyzed by multivariate analysis and multiple linear regression analysis. Arsenic concentrations in cord blood were significantly lower than those in maternal blood. A significant positive correlation was shown betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 16 publications
6
34
2
Order By: Relevance
“…72 Similarly, in a study on the general population in Dalian, China, infants born to mothers with arsenic blood levels greater than 5.3 μg/L weighed 220 g less than those infants whose mothers had lower blood arsenic levels. 73 This study also demonstrated a significant, strong correlation between maternal arsenic and cord blood arsenic. These studies indicate that low levels of arsenic can have direct impacts on the growth of newborns.…”
Section: ■ Discussionsupporting
confidence: 61%
“…72 Similarly, in a study on the general population in Dalian, China, infants born to mothers with arsenic blood levels greater than 5.3 μg/L weighed 220 g less than those infants whose mothers had lower blood arsenic levels. 73 This study also demonstrated a significant, strong correlation between maternal arsenic and cord blood arsenic. These studies indicate that low levels of arsenic can have direct impacts on the growth of newborns.…”
Section: ■ Discussionsupporting
confidence: 61%
“…Yet, no associations were detected for 71 female newborns. In another study, 125 women were recruited from a primary delivery center in Dalian City (Guan et al, 2012). Total arsenic was measured in maternal blood collected upon admission for delivery (median = 5.30 μg/L, range = 0- ~25) and umbilical cord blood collected prior to passage of the placenta (median = 3.71 μg/L, range = 0- ~25).…”
Section: Resultsmentioning
confidence: 99%
“…Though the authors of these cross-sectional studies employed hospital delivery records and biomarkers of exposure, the use of total blood arsenic raises concern (Guan et al, 2012; Xu et al, 2011). Total blood arsenic incorporates both iAs as well as the comparatively non-toxic organic arsenic species (Akter et al, 2006) to which humans are exposed when consuming seafood (Le et al, 1994; Navas-Acien et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…1 Data from exposure assessment studies demonstrate that arsenic readily crosses the placenta and that fetal exposure is highly correlated with maternal exposure. [2][3][4][5] Evidence from epidemiological studies shows that early life exposure to arsenic is associated with increased risk of adverse health outcomes later in life. For instance, a large ecological study in Chile reported that people in Antofagasta who were exposed to high concentrations of arsenic either prenatally or in early childhood had significantly higher mortality from lung cancer and bronchiectasis compared with people from other parts of the country.…”
Section: Introductionmentioning
confidence: 99%